Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Di Kantor Dinas Lingkungan Hidup Kota Parepare - Anastasia D’ornay; Ulfa Natsir (Economics and Digital Business Review, 2024)
This research aims to determine the influence of the work environment on employee performance at the Parepare City Environmental Service Office. The method used in this research is a survey using a questionnaire as a data collection instrument. The sample for this research is employees who work at the Parepare City Environmental Service. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The findings of this research will provide an in-depth picture of employee experiences in different work environments, as well as their impact on employee performance. This right is expected to provide qualitative and contextual insight in explaining the relationship between the work environment and employee performance at the Parepare City Environmental Service. It is hoped that the results of this research can provide practical recommendations to the management of the Environmental Service in designing more effective strategies for creating a work environment that motivates employees and improves employee performance. Apart from that, it is also hoped that this research can provide theoretical contributions to the field of study of human resource management and organizational performance.